Desexo, fotografía e literatura en Blanco Amor - Lema, Carlos (Madrygal. Revista de Estudios Gallegos, 2009)
The photography, in the case of Eduardo Blanco Amor, balances between the liking and the Art. That maladjustment to the formalized language is the expression of a identitity hesitation: the subject resists to the work notion, is against the institucionalizer power of the community. That context, the potentiality of desire is transformed into a destabilizing mechanism of the speeches that locates to the individual in a position of social incomodidad. The narrative work of Blanco Amor also expresses that conflict: the Castilian like institucionalizador power, Galician like style that perforates the literary Art and spills the sense (the convention).